ANALISA RCM PADA MOTOR DIESEL PENGGERAK GENERATOR DAYA 320 kVA SUMBER KELISTRIKAN DI HOTEL SAPADIA ROKAN HULU - Legisnal Hakim (Jurnal APTEK, 2014)
When the supply of electricity in a hotel is off or at a local electricity grid is not able to distribute to thehotel, the hotel shall provide its own power supply using a generator driven by a Diesel Engine. Motor dieselis the motor that is also called Compression Ignition ("Compression - Ignition engine"). Diesel generator asa driver that is in use at Hotel Sapadia Type Cummins Diesel Engine NTA 855 A. are very susceptible tomalfunction, which causes many malfunctions caused by human error, the age factor, system maintenance,and operation of the tool. The cause of the failure is also due to a lack of planning on the part ofmanagement to make strategic plans for program maintenance